Strategic Tendencies and Priorities of Development of Aquaculture in Russia - K. L. Kudryashova (Управленческое консультирование, 2018)
Member States of the United Nations in the autumn of 2015 approved the Agenda for Sustainable Development for the period until 2030. The Agenda also establishes goals for the contribution and methods of fishing and aquaculture production to achieve food security and adequate nutrition in the use of natural resources. Meeting the ever-increasing demand for fish products in accordance with the UN Agenda for the period until 2030 will be a development priority. The main world tendencies in the development of the fishing industry complex are studied and some strategic priorities for the development of the aquaculture industry in Russia.